Refleksi Pengalaman Transendental dalam Seni Kontemporer (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
Transcendental is incomprehensible matter that regarded as mystical and abstract. Not all transcendental experiences can feel and experience events with astral beings. The fear of transcendental experiences is a matter of personal experience. The experience experienced is seeing, disturbed by astral beings. This final project, entitled Selamat Jalan, applies a symbolic narrative approach in presenting a new perspective on transcendental experiences by creating a creative process through journaling stories about experiences that have been experienced. With a contemporary art approach, it is implemented in installation works that present aesthetic objects with charcoal paintings. This work is a reflection for artists by sublimating through works of art the fear of transcendental experiences. This work is also a form of courage in being afraid of the comments of others who do not believe in the supernatural or astral beings. The sublimation of this work is poured into a work of installation art.